Metabolomic, hormonal and physiological responses to hypoglycemia versus euglycemia during exercise in adults with type 1 diabetes. Issue 1 (5th October 2020) - McCarthy, Olivia; Pitt, Jason; Churm, Rachel; Dunseath, Gareth J; Jones, Charlotte; Bally, Lia; Nakas, Christos T; Deere, Rachel; Eckstein, Max L; Bain, Stephen C; Moser, Othmar; Bracken, Richard M
Abstract : Introduction: This study sought to compare the metabolomic, hormonal and physiological responses to hypoglycemia versus euglycemia during exercise in adults with type 1 diabetes (T1D). Research design and methods: Thirteen individuals with T1D (hemoglobin; 7.0%±1.3% (52.6±13.9 mmol/mol), age; 36±15 years, duration diabetes; 15±12 years) performed a maximum of 45 min submaximal exercise (60%±6% V̇O2max ). Retrospectively identified exercise sessions that ended in hypoglycemia ((HypoEx) blood glucose (BG)≤3.9 mmol/L) were compared against a participant-matched euglycemic condition ((EuEx) BG≥4.0, BG≤10.0 mmol/L). Samples were compared for detailed physiological and hormonal parameters as well as metabolically profiled via large scale targeted ultra-high-performance liquid chromatography coupled to tandem mass spectrometry. Data were assessed using univariate and multivariate analysis techniques with false discovery rate adjustment. Significant results were considered at p≤0.05. Results: Cardiorespiratory and counterregulatory hormone responses, whole-body fuel use and perception of fatigue during exercise were similar under conditions of hypoglycemia and euglycemia (BG 3.5±0.3 vs 5.8±1.1 mmol/L, respectively p<0.001). HypoEx was associated with greater adenosine salvage pathway activity (5'-methylthioadenosine, p=0.023 and higher cysteine and methionine metabolism), increased utilization of glucogenic amino acids (glutamine, p=0.021, alanine, aspartate and glutamate metabolism and homoserine/threonine, p=0.045) and evidence of enhanced β-oxidation (lower carnitine p<0.001, higher long-chain acylcarnitines). Conclusions: Exposure to acute hypoglycemia during exercise potentiates alterations in subclinical indices of metabolic stress at the level of the metabolome. However, the physiological responses induced by dynamic physical exercise may mask the symptomatic recognition of mild hypoglycemia during exercise in people with T1D, a potential clinical safety concern that reinforces the need for diligent glucose management. Trial registration number: DRKS00013509.